"Daughterly texts": fathers and their daughters in Zoë Wicomb's You Can't Get Lost in Cape Town and Chimamanda Ngozi Adichie's Half of a Yellow Sun. Issue 1 (28th July 2020) - Ngwira, Emmanuel
Abstract: This article analyzes how the relationship between fathers and daughters is portrayed in Zoë Wicomb's You Can't Get Lost in Cape Town and Chimamanda Ngozi Adichie's Half of a Yellow Sun . The paper observes that in these texts, daughters occupy spaces, both in and outside the home, that are usually considered reserved for sons who are often groomed as heirs to their fathers' worlds. Drawing on discourse on women, history and the nation, particularly the work of Tiyambe Zeleza and Elleke Boehmer, among other scholars, this paper argues that by placing daughters in spaces often thought to be for sons, both Wicomb and Adichie challenge the marginalization of women in history and narratives of the nation. The paper further shows that instead of perpetuating their fathers' legacies, daughters in the two texts chart for themselves paths that divert from their fathers' aspirations. In that way, the daughters' lives become counter-texts not only to their fathers' lives and aspirations but also to the general patriarchal imaginings of history and the nation that the fathers represent.